Investigation of HAPs Propagation Channel for Wireless Access in a Tropical Region at Ka-Band - Felix Obite; Jafri Din; Kamaludin Mohammad Yusof; Basliza M. Noor (International Journal of Electrical and Computer Engineering (IJECE), 2017)
In the last few years, High Altitude Platforms (HAPs) have attracted considerable effort due to their ability to exploit the advantages of satellite and terrestrial-based systems. Rain attenuation is the most dominant atmospheric impairment, especially at such frequency band. This paper addresses the modelling of rain attenuation and describes a propagation channel model for HAPs at Ka-band to provide efficient and robust wireless access for tropical regions. The attenuation due to rain is modeled based on three years measured data for Johor Bahru to estimate the actual effect of rain on signals at Ka band. The radio propagation channel is usually characterized as a random multipath channel. Specifically, a statistical derivation of probability distribution function for Rayleigh and Rician fading channels are presented. The model consists of multiple path scattering effects, time dispersion, and Doppler shifts acting on the HAPs communication link. Simulation results represent the fading signal level variations. Results show perfect agreement between simulation and theoretical, thereby conforming to the multipath structures. The information obtained will be useful to system engineers for HAPs link budget analysis in order to obtain the required fade margin for optimal system performance in tropical regions.